Educational Quality from the Perspective of Cultural Identity (Docentes 2.0 Journal, 2023)
Perfection and educational quality is not static point or an endpoint reached at a certain moment. The essay's objective was to discover and analyze the truth of the cultural roots to identify those values that characterized them as Mexicans before the conquest. This essay is framed under the inductive method, in the humanistic paradigm, with a qualitative approach, and with a topical narrative design, with which it is intended to identify cultural arguments that affect the educational quality of Mexico in Basic Education, as well as present some improvements in the educational process. There are many aspects, approaches, proposals, and educational models that researchers, pedagogues, writers, philosophers, and scholars in educational matters have formulated and that have been implemented over the years in the Educational System of our country, which, without a doubt, They have greatly favored the progress of education in different ways. Still, they have also presented shortcomings and weaknesses that have yet to allow us to fully resolve the educational quality that we so longed for and the problems that we experience daily in institutions.
Keywords: Educational quality; perspective; cultural identity